The incidence and prognosis of thymic squamous cell carcinoma: A Surveillance, Epidemiology, and End Results Program population-based study. Issue 15 (16th April 2021) - Wu, Jingyi; Wang, Zhijun; Jing, Caibao; Hu, Yang; Yang, Bing; Hu, Yanping
Abstract: Background: Thymic carcinoma represents a rare type of malignant mediastinal tumor and has been the subject of controversy. Although independent prognostic factors related to thymic carcinoma have been investigated previously, few studies have focused specifically on the survival outcomes associated with thymic squamous cell carcinoma (TSCC). This study aims at presenting a survival analysis in this rare malignant disease at population level. Methods: We extracted the data of 216 patients with TSCC recorded from 1973 to 2015 from the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute. The patients' demographic features, clinical traits, and treatment factors were analyzed in order to identify prognostic factors, which correlate overall survival using the Kaplan–Meier method as well as a multivariate Cox regression model, for TSCC. Results: The majority of patients were male, Caucasian, married, and insured. Furthermore, 58.3%, 54.6%, and 59.7% of patients TSCC underwent surgery, radiotherapy, and chemotherapy respectively. In a multivariate analysis, age of diagnosis (hazard ratio [HR]: 1.022, 95% confidence interval [CI]: 1.003–1.040, P  = .020), surgical treatment (HR: 0.282, 95% CI: 0.164–0.484, P  = .000), and stage (regional vs distant HR: 0.532, 95% CI: 0.324–0.872, P  = .013; localized vs distant HR: 0.297, 95% CI: 0.133–0.664, P  = .003) correlated with increased overall survival, whereas adjuvant therapy, including chemotherapy and radiotherapy, did not correlate with survival. Among surgically treated patients, age of diagnosis and stage were associated with better overall survival, while chemotherapy and radiotherapy did not contribute significantly to overall survival. Conclusion: Surgery, age of diagnosis, and stage were associated with better overall survival among TSCC.